Does digital-economy development improve air quality in Border Regions? Empirical evidence from 188 Chinese cities - Huifu Li; Mengling Li; Xu Li; Danyang Li (PLoS ONE, 2026)
Using panel data from Chinese inter-provincial border cities from 2014 to 2023, this study systematically analyzes the impact of digital-economy development on air quality in border regions. Empirical results show that the digital economy significantly improves air quality in such regions, with this effect being more prominent in non-contiguous, poverty-stricken areas and regions with lower levels of coordinated regional development. In addition, the digital economy exhibits significant positive spatial-spillover effects on air quality in adjacent regions, effectively inhibiting cross-regional diffusion of atmospheric pollution. Mechanism analysis further indicates that the digital economy achieves air-quality improvement in border regions primarily through breaking down regional market segmentation and enhancing environmental tracking and regulatory capacity. This study’s findings help address the challenge faced by developing countries during industrial transformation, namely, that the border regions tend to become “pollution havens.” The findings contribute to improving overall environmental-governance effectiveness.